Jenis Tumbuhan Non-Kayu sebagai Produk Kerajinan yang Dikomersialisasikan di Kabupaten Padang Pariaman Provinsi Sumatera Barat - Qurrata A'yuni A'yuni; Reki Kardiman; Rijal Satria; Resti Fevria (Symbiotic: Journal of Biological Education and Science, 2024)
Non-timber forest products (NTFPs) are all types of forest products other than wood which provide multi-purpose benefits for the community, especially local communities who live around the forest. NTFP products are the main focus for alternative economic value of forests, NTFP demand can be used as a reference for management. One potential use of NTFPs is handicraft products that are bought and sold in economic centers, but the various types of NTFPs and their derivative products are still unknown. This research investigates the use of NTFPs for craft products in Padang Pariaman Regency, including the species of plants used, the types of craft products, and market potential. The survey was carried out in five places in Padang Pariaman Regency, selected using purposive sampling. Four types of NTFP plants were found which were used to make 27 types of craft products, namely Pandanus tectorius, Cocos nucifera L., Bambusa spp., and Calamus spp. Most handicraft products are produced from rattan plants, and the highest market potential is obtained by coconut-based craft products with a percentage of 83%. This data can be a reference for LPHN or forest managers around the Padang Pariaman Regency area.